RELASI ISLAM DAN PANCASILA SEBAGAI SISTEM HUKUM: KAJIAN KEPUTUSAN MUKHTAMAR MUHAMMADIYAH KE - 47 DI MAKASSAR - Syafruddin, Syafruddin; Hasanah, Siti; Arzhi Jiwantara, Firzhal; Mukhlishin, Mukhlishin; Sarip, Sarip (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
The Republic of Indonesia is based on Pancasila as an agreement between all elements of the nation with various ethnic groups, languages ​​and various religions. The birth of Pancasila is considered by some Muslims to be an agreement between the founding fathers of the nation. Pancasila is considered very appropriate and appropriate to accommodate all races, ethnicities and religions in Indonesia. This is what then attracts researchers to examine more deeply Muhammadiyah's thinking about the relationship between Islam and Pancasila and what the relationship between Islam and Pancasila as a legal system is from Muhammadiyah's perspective. According to Muhammadiyah, the Pancasila state can be realized as